067 Anticoagulation in patients with atrial fibrillation and a permanent pacemaker remains poor as general practitioners are not informed of the arrhythmia. (16th May 2012) - Vassiliou, V; Farag, A; McIntosh, E; Williams, I
Abstract : Introduction: Electrocardiographic recognition of the underlying rhythm in patients with a permanent pacemaker can be very difficult. Atrial fibrillation/flutter in particular might go unreported and the paced rhythm can obscure recognition of atrial arrhythmias by the General Practitioners (GPs). Furthermore, in our region, pacing clinics are often run at the hospital independently of GPs, even if the patients are no longer followed-up in the cardiology outpatient clinic. Identification of new Atrial Fibrillation/Flutter might not be communicated adequately to GPs, therefore depriving patients from appropriate anticoagulation. Methods: We retrospectively reviewed records of 282 patients who attended routine outpatient pacing clinics in our institution over a 2-month period and identified patients with atrial arrhythmias suitable for anticoagulation. We considered all patients with persistent Atrial Fibrillation/Flutter or paroxysmal Atrial Fibrillation/Flutter >30 min (all 4 groups referred to as AF in the text) with a calculated CHA2DS2-Vasc ≥2 as eligible for anticoagulation. The electronic records and/or case notes were reviewed establishing whether the patients were anticoagulated and whether GPs had been informed of the diagnosis of AF. Results: 282 cases (men=124) were reviewed and 95 patients (33.7%) were noted to have AF (men=40, age median=83, mean CHA2DS2-Vasc=3.7). 72 patients (75.8%) had persistent AF/Flutter and 23 patients (24.2%) had paroxysmal AF/Flutter. For 24/95 (25.3%) patients, AF was first identified after pacemaker implantation at a routine pacing check and the GP (or cardiologist) had not been informed of this diagnosis. Therefore, these patients were never considered for anticoagulation. 44/95 (46.3%) were anticoagulated with warfarin and 13/95 (13.7%) were unable to take or refused warfarin due to: frequent falls (3), general fragility (1), dementia (1), gastric cancer (1), gastric bleed (1), subdural haematoma (1), hepatocellular carcinoma (1), dual antiplatelets for coronary stents (1), and due to patient refusal (3). There was no significant difference in informing GPs between paroxysmal and persistent AF/Flutter (χ 2 p=0.16), men and women (χ 2 p=0.25). Conclusions: We have shown that it is very common to identify AF following pacemaker implantation and the incidence of AF in patients with permanent pacemakers is much higher than historical age-matched population (33.7% vs 10.0%). Anticoagulation in this group remains sub-optimal. Up to 25.3% of the patients are found to have AF suitable for consideration of anticoagulation, however this information is not passed to the GPs for further action. A routine pacing clinic review offers an ideal opportunity for identification of AF. Liaising with the GP however, is essential to optimise anticoagulation uptake in this population.